Acidipropionibacterium acidipropionici, a propionate-producing bacterium, contributes to GPR41 signaling and metabolic regulation in high-fat diet-induced obesity in mice - Miyamoto, Junki; Ando, Yuna; Yamano, Mayu; Nishida, Akari; Murakami, Kota; Kimura, Ikuo (Frontiers in Nutrition, 2025)
Obesity is a major healthcare problem worldwide and is induced by excess energy intake, resulting in gut microbial composition and microbial diversity changes. Through fermentation of dietary fibers, short-chain fatty acids (SCFAs) act as host energy sources and signaling molecules via G protein-coupled receptors such as GPR41. Acidipropionibacterium acidipropionici is widely used in many applications; however, in vivo studies on the beneficial effect of A. acidipropionici via propionate production and host energy homeostasis are unclear. Therefore, this study aimed to investigate the beneficial metabolic effects of A. acidipropionici by focusing on GPR41 signaling in a high-fat diet (HFD)-induced obesity mouse model. Here, we demonstrated that A. acidipropionici OB7439 improved host metabolism in HFD-induced obesity in mice. The intake of A. acidipropionici OB7439 improved metabolism in HFD-induced obese mice by increasing propionate production, regulating glucose tolerance, and inhibiting hepatic inflammation via GPR41 signaling. Our findings shed light on the potential of using A. acidipropionici OB7439 as an SCFA producer for the prevention and treatment of metabolic disorders. Based on these results, we suggest that A. acidipropionici may be a potential therapeutic bacterium that inhibits obesity and modulates the gut microbial community.